Towards A Sanitation Selection Algorithm For Enhancing Decentralized Service Delivery - Niwagaba, B. C.; Kinobe, J. R.; Atwine, E.; Kisaka, J. N. (WEDC, Loughborough University, 2006)
In Uganda, sanitation coverage is estimated at 53% and 39% for urban and rural areas respectively. The national coverage is 41%. Lack of proper sanitation potentially leads to environmental health problems, which in many cases cost lives and impact on health of a community and family income as more money is spent on medication. This leads to a vicious circle of poverty. The objective of this study was to collect information on the current practices in selection of sanitation arrangements and use it to develop a simple algorithm for use by decision makers and district staff to advise households on selection of appropriate sanitation systems. Currently, there is no streamlined criterion used. People select systems based on what they are used to. Consequently, traditional pit latrines are the commonest sanitation system used. These toilet systems however, are disadvantageous due to: difficult soils (rocky, collapsing formations and areas with high water table); when full, require that new pits are dug, which is expensive and in the dense settlements this is inhibited by lack of space for new pits. As a starting point, we have proposed a simple algorithm that can be used by decentralized districts to give guidance to households in the selection of sanitation systems. The principle of the sanitation ladder, where people choose from the whole range of options, and select systems based on site conditions, affordability as well as user acceptance and perceptions applies. At the next phase, we intend to carry out detailed consultations to get specific information on user preferences, develop costs for all categories and package the information in an easy to use document for awareness creation, advocacy and promotion of sanitation.